2015
DOI: 10.1530/eje-14-0863
|View full text |Cite
|
Sign up to set email alerts
|

Lactonase activity and status of paraoxonase 1 in Chinese women with polycystic ovarian syndrome

Abstract: Objective: To study the relationship between the lactonase activities and status of paraoxonase 1 (PON1) and its association with the PON1 genetic polymorphisms in women with polycystic ovarian syndrome (PCOS). Design: A case-control study. Methods: A total of 455 PCOS patients and 441 control women were included in this study. The lactonase activities and concentrations of PON1 were assayed using 5-thiobutyl butyrolactone (TBBL) and 7-O-diethylphosphoryl-3-cyano-4-methyl-7-hydroxycoumarin (DEPCyMC) respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 60 publications
1
22
0
Order By: Relevance
“…Stress Markers. The lactonase activity and levels of PON1 were determined using 5-thiobutyl butyrolactone (TBBL) and 7-O-diethylphosphoryl-3-cyano-4-methyl-7-hydroxycoumarin (DEPCyMC) as a substrate, respectively, based on the measurement described in our earlier study [16]. A normalized lactonase activity ðNLAÞ = TBBL activity ðU/mLÞ × 1000/ DEPCyMC activity (mU/mL) [14,16].…”
Section: Analysis Of Pon1 Activity Metabolic and Oxidativementioning
confidence: 99%
See 1 more Smart Citation
“…Stress Markers. The lactonase activity and levels of PON1 were determined using 5-thiobutyl butyrolactone (TBBL) and 7-O-diethylphosphoryl-3-cyano-4-methyl-7-hydroxycoumarin (DEPCyMC) as a substrate, respectively, based on the measurement described in our earlier study [16]. A normalized lactonase activity ðNLAÞ = TBBL activity ðU/mLÞ × 1000/ DEPCyMC activity (mU/mL) [14,16].…”
Section: Analysis Of Pon1 Activity Metabolic and Oxidativementioning
confidence: 99%
“…Some PON1 genetic variations have been reported to influence the enzyme concentration and specific activity of PON1 [10,15]. The −108C/T variant of the PON1 gene influences PON1 expression and the 192Q/R polymorphism affects PON1 activities [9,10,16]. The PON1 R isoform hydrolyzes lipid peroxides in vitro less efficiently than does the Q isoform [9].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our recent study demonstrated that E 2 levels correlated positively with intrinsic HDL oxidation levels in patients with PCOS . E 2 or oestrogen may increase of HDL binding and oxidized lipid transport by elevating apoA1 levels, which may contribute to increase circulating TOS and OSI because HDL is the major carrier of lipid hydroperoxides …”
Section: Discussionmentioning
confidence: 91%
“…Our previous studies demonstrated that patients with HA have higher serum MDA levels and more severe impairment of high‐density lipoprotein (HDL) antioxidant activities than those without HA . In addition, the lactonase activities and levels of PON1 were higher, and HDL‐associated platelet‐activating factor acetylhydrolase (PAF‐AH) activities were lower in patients with PCOS than in controls . Furthermore, the PAF‐AH G994T gene mutation and the PON1 Q192R gene variation are risk factors for PCOS .…”
Section: Introductionmentioning
confidence: 99%
“…Oligo- or anovulation (OA) was assessed as oligomenorrhea (i.e., fewer than eight cycles per year). Biochemical or clinical hyperandrogenism (HA) was assessed by total testosterone (TT) levels above the 95th percentile of the levels (2.60 nmol/l) detected in a group of normal menstruating women with normal cycles, hirsutism with a modified Ferriman–Gallwey (F-G) score of more than 6 and/or clinical presence of obvious acne [4, 27, 28]. Polycystic ovaries (PCOs) were confirmed if there were 12 or more follicles in each ovary measuring 2–9 mm in diameter and/or increased ovarian volume (>10 mL) by ultrasonic examination.…”
Section: Methodsmentioning
confidence: 99%